Rapid Electrochemical Phosphating at Room Temperature - Ma, L.; Yang, X.J.; Peng, C.; Yang, Q. (Asian Journal of Chemistry, 2014)
The application of electrochemical method in phosphating treatment accelerates ion diffusion at room temperature. By applying this method the process can be completed within 10 min. After careful screening, the crystalline phosphate film exhibited the best comprehensive performance, under the condition where manganous dihydrogen phosphate concentration was 30-50 g/L, zinc nitrate concentration was 50-70 g/L, current density was 1.00-1.50 A dm-2 and electrochemical phosphorization time was 5-7 min at room temperature. In addition, the analytical studies indicated that the strong corrosion resistant phosphate film, which mainly contains O, Zn, P, Mn and Fe, is uniform compact and easy for the coat to adhere.